78.8k views
3 votes
-6x+4+3x-2?

7(x + 2) + 3 = 73

3-7x+4x-10

4k-14+3k=21

5(-4x+2)+9x

h-6+7h=42

4(7x-8) + 6(5x+10)

3(n+5)+2=26

-6x+4+3x-2? 7(x + 2) + 3 = 73 3-7x+4x-10 4k-14+3k=21 5(-4x+2)+9x h-6+7h=42 4(7x-8) + 6(5x-example-1
User Jalen
by
5.0k points

2 Answers

6 votes

Answer:

Explanation:

-6x+4+3x-2? 7(x + 2) + 3 = 73 3-7x+4x-10 4k-14+3k=21 5(-4x+2)+9x h-6+7h=42 4(7x-8) + 6(5x-example-1
User Harishbb
by
4.6k points
4 votes

Answers:

-6x+4+3x-2= -6x+3x+4-2= -3x+2

7(x + 2) + 3 = 73

Multiply the bracket by 7

7x+14+3= 73

7x+17= 73

7x= 73-17

7x=56

Divide by 7

7x/7= 56/7

x= 8

3-7x+4x-10= -7-3x

4k-14+3k=21

7k-14= 21

Move -14 to the other side. Sign changes from -14 to +14.

7k-14+14= 21+14

7k= 35

divide by 7

7k/7= 35/7

k= 5

5(-4x+2)+9x

Multiply the bracket by 5

-20x+10+9x= -11x+10

h-6+7h=42

8h-6= 42

Move -6 to the other side.

8h-6+6= 42+6

8h= 48

divide by 8

8h/8= 48/8

h= 6

4(7x-8) + 6(5x+10)

Multiply the first bracket by 4

Multiply the second bracket by 6

28x-32+30x+60

= 58x+28

3(n+5)+2=26

Multiply the bracket by 3

3n+15+2= 26

3n+17= 26

3n+17-17= 26-17

3n= 9

divide by 3

3n/3= 9/3

n= 3

User Thoughtarray
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.